1999
DOI: 10.1021/om980762r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of Unsolvated Triple-Decked Bent Metallocenes of Divalent Europium and Ytterbium

Abstract: The europium and ytterbium complexes of formula [(C5Me5)Ln]2(μ-η8:η8-C8H8) have been synthesized and structurally characterized to determine the dependence of the (ring centroid)−metal−(ring centroid) angles on the size and electron configuration of the metal. YbI2(THF)2 reacts with KC5Me5 and K2C8H8 in THF to form [(C5Me5)Yb(THF)]2(μ-η8:η8-C8H8), 1, in 80% yield. 1 can be readily desolvated at 30 °C and 10-7 Torr to afford [(C5Me5)Yb]2(μ-η8:η8-C8H8), 2, in 80% yield. 2 crystallizes from toluene and consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 25 publications
7
56
0
2
Order By: Relevance
“…It is unclear how reliable such estimates are. For example, a recently reported bent structure for a triple‐decker sandwich without alkyl substituents at the central C 8 H 8 ring has been taken as evidence against the importance of vdW attractions 176. Even if weak attractive interactions are important, this implies that the other factors involved (covalent bonding, core polarization, ligand repulsion) act together to provide a very shallow bending potential curve,27 such that the weak dispersive forces may become decisive.…”
Section: Bonding Descriptions and Modelsmentioning
confidence: 99%
“…It is unclear how reliable such estimates are. For example, a recently reported bent structure for a triple‐decker sandwich without alkyl substituents at the central C 8 H 8 ring has been taken as evidence against the importance of vdW attractions 176. Even if weak attractive interactions are important, this implies that the other factors involved (covalent bonding, core polarization, ligand repulsion) act together to provide a very shallow bending potential curve,27 such that the weak dispersive forces may become decisive.…”
Section: Bonding Descriptions and Modelsmentioning
confidence: 99%
“…Offensichtlich ist dann die Gröûe der Liganden von besonderer Bedeutung. [176] Selbst wenn schwache anziehende Wechselwirkungen wichtig sind, impliziert dies, dass die anderen beteiligten Faktoren (kovalente Bindung, Rumpfpolarisation, Ligandenabstoûung) so zusammenwirken, dass eine sehr flache Potentialmulde für die Bindungswinkeldeformation entsteht, [27] was letztlich dazu führt, dass die schwachen dispersiven Kräfte entscheidend werden. Während mehrere permethylierte Komplexe des Typs [MCp* 2 ] (M Sm, Eu, Yb, Ba; Cp* h 5 -C 5 (CH 3 ) 5 ) im Festkörper gewinkelte Strukturen aufweisen (potentielle Einflüsse durch intermolekulare Wechselwirkungen sind dabei zu beachten, siehe Abschnitt 2.1), bedingen gröûere Alkylsubstituenten an den Cyclopentadienlyringen aufgrund des sterischen Anspruches der Liganden schlieûlich lineare Metallocenstrukturen.…”
Section: Die Rolle Der Ligandenabstoûungunclassified
“…Divalent lanthanocenes [(C 5 Me 5 ) 2 Ln] with sandwich structure have attracted considerable attention in the past few decades. [21] Evans et al reported triple-decker bent metallocenes complexes of divalent lanthanides [(m-h 8 [22] Recently, Edelmann et al reported a rare tetradecker sandwich complex of a divalent lanthanide, namely, [(C 5 Me 5 )Yb(m-h 8 [23] Half-sandwich bistetramethylaluminate complexes of the rare earth metals were reported by Anwander et al [24] Complexes with one, (2), Sm1À N2 2.550(2), Si1ÀN1 1.693 (2), Si1ÀN2 1.701 (2), K1ÀO1 2.752 (2), K1À C14 3.222 (3), K1ÀC16 3.077 (3), K1ÀC17 3.094 (3), K1ÀC15 3.114 (3), K1À C18 3.168 (3), K1ÀX1 A 2.829, K1ÀX1B 2.925; N1-Sm1-N1A 180.00 (10), N2-Sm1-N2A 180.00 (9), N1-Sm1-N2 63.32 (7). (2) LnÀN2 2.550 (2) 2.442 (2) Si1ÀN1 1.693 (2) 1.703 (2) Si1ÀN2 1.701 (2) 1.696 (2)…”
Section: Resultsmentioning
confidence: 99%